Formulation, Characterization and Evaluation to Establish the Bioavailability of Gastroretentive Mucoadhesive Dosage of Atenolol in Human Subjects with Possible In-Vitro-In-Vivo Correlation: Gastroretentive Mucoadhesive Dosage Form of Atenolol - Kumar, Kiran; Gurunath, S.; Rao, Madhusudan; Ajitha, M. (Iranian Journal of Pharmaceutical Sciences, 2020)
This study was planned to formulate, characterize, and evaluate to establish the bioavailability of gastroretentive mucoadhesive dosage of atenolol in human subjects with possible in-vitro-in-vivo correlation. In this investigation gastroretentive mucoadhesive dosage of Atenolol was formulated using HPMCK4M, chitosan and Isabgul husk by wet granulation technique. The prepared tablets were subjected to physical evaluation, in-vitro drug release, and in-vivo X-ray studies, followed by the pharmacokinetic study in human volunteers. All the prepared tablets showed physicochemical properties within the limits and good in-vitro mucoadhesion. Formulation F2 was selected based on the in-vitro characteristics and in-vivo radiographic studies by replacing part of the drug by adding barium sulphate. From the radiographic studies it was found that the F2 could be successfully retained in stomach for more than 6 hours. Pharmacokinetic studies showed a significant improvement in AUC0-14; 6414.93 ± 58.221 ng.h/mL (p < 0.05) when compared to reference AUC0-14; 4752.18 ± 76.759 ng.h/mL in healthy human volunteers with good in vitro-in vivo correlation. Based on in-vitro characteristics and in-vivo radiographic studies, F2 was selected as optimized gastroretentive mucoadhesive dosage form with improved bioavailability for better patient compliance and disease management.